Perencanaan Guru IPS dalam Menggunakan Media dan Bahan Ajar Berbasis Digital: Studi Kasus di SMP Negeri 12 Kota Bengkulu - Vivia A Wijaya; Adisel Adisel; Desi Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to describe the planning of social studies teachers in using digital-based media and teaching materials and describe the social studies teacher's obstacles in using digital-based media and teaching materials at SMP Negeri 12 Bengkulu City. This research is a field research with a descriptive qualitative approach. Data collection techniques in this study were carried out by observation, interviews and documentation. The data analysis technique uses data reduction, data display, and verification. The results of the study found that in using digital-based media and teaching materials in learning planning by social studies teachers it had been carried out well but could not be said to be successful because of the lack of understanding of social studies teachers in using digital-based media and teaching materials properly and correctly, this can seen from the planning made by social studies teachers, some have not paid attention to indicators of planning elements, both in terms of scientific, relevant, systematic, consistent, adequate, actual conceptual, flexible and comprehensive. The social studies teacher's obstacles in using digital-based media and teaching materials include less proficient teachers, inadequate facilities and infrastructure, difficulties in designing digital-based media and teaching materials and the skills and creativity of social studies teachers are still not good.